Mepolizumab asthma treatment failure due to refractory airway eosinophilia, which responded to benralizumab. Issue 5 (1st April 2021) - Cook, Alistair; Harrington, John; Simpson, Jodie L.; Wark, Peter
Abstract: Monoclonal antibodies directed against interleukin (IL)‐5, such as mepolizumab and benralizumab, are an effective and established treatment for severe eosinophilic asthma. Here, we present a patient with eosinophilic asthma with a partial clinical response to mepolizumab initially, as measured by these biomarkers, who when investigated was found to have refractory airway eosinophilia. Escalation of the mepolizumab dose led to further but still only partial response. A treatment trial with benralizumab was more successful and led to suppression of airway eosinophilia. We review the literature, focusing on eosinophil biology at the tissues and the different mechanisms of action of the two agents. Abstract : Monoclonal antibodies directed against interleukin (IL)‐5, such as mepolizumab and benralizumab, are an effective and established treatment for severe eosinophilic asthma. Here, we present a patient with eosinophilic asthma with a partial clinical response to mepolizumab, although with refractory airway eosinophilia, who did not fully respond to dose escalation. A treatment trial with benralizumab was more successful and led to suppression of airway eosinophilia.